PENERAPAN PEMBELAJARAN ETNOMATEMATIKA DALAM JAJANAN TRADISIONAL WAJIK UNTUK MENINGKATKAN KEMAMPUAN BELAJAR DI KELAS V MATERI VOLUME BALOK DENGAN KUBUS SATUAN - Putri Thalia Fitria; Julianto; Fathul Bari; Siti Maslikah; Fitria Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was conducted with the aim of determining the learning outcomes of cube and block volume material through the RME approach in traditional wajik snacks in class V SDN Petemon Surabaya with 27 students as research subjects. The method used in this study is Classroom Action Research which includes pre-cycle and 2 cycles of data collection techniques using tests and response questionnaires. The two cycles are used to determine the improvement in student learning outcomes. Learning instruments are designed and developed based on the assumption of the learning process and using the Realistic Mathematics Education (RME) approach. This journal will discuss the results of the 2 cycles that have been compiled and implemented by researchers, solving problems in the form of the number of unit cubes that can fill a pan with unit cube and block media. The results of the learning process activities show that through a series of activities created by researchers, it can help improve students' learning abilities in understanding the concept of cube and block volume. The average student understanding ability between cycles I and II increased from 80.07% to 93.33%. Students also showed enthusiasm in learning when interspersed with questions and rewards for those who could answer because it could increase students' enthusiasm in understanding the material.